Pengaruh Media Busy Board terhadap Perkembangan Motorik Halus Anak di TK Iqra’ Tunggul Hitam Padang - Afriani, Afni; Angraini, Vivi (Darul Yasin Al Sys, 2024)
Fine motor skills are acquired through practice and education. Defined as precision movements that use small muscles or specific body parts. From observations made at Iqra' Kindergarten, it can be seen that children's fine motor development is still lacking. The aim of this research is to evaluate the extent to which busy board media can help kindergarten students at TK Iqra' ANGKAL Hitam Padang in developing their fine motor skills. This research stands out for its emphasis on quantitative elements and using an experimental research approach. The researchers used word and action assessments to collect data. To test the data, homogeneity and normality checks were carried out. The average score of the experimental class was 14.17, while the control group's score was 12.75, based on research findings before and after the test. The significance level of 0.05 is somewhat exceeded by the two-sided p value of 0.009. As a result, we can say that the difference between the experimental group and the control group is statistically significant. As a result, there were striking differences between the experimental group and the control group. Thus, it can be concluded that the null hypothesis (Ho) is refuted and the alternative hypothesis (Ha) is validated. The results showed that there were significant differences in the fine motor skills of experimental and control group children aged 5-6 years. This shows that the Media Busy Board is an effective way to help teenagers in this age range improve their fine motor skills.